DAMPAK GREEN PSYCHOLOGICAL CLIMATE DAN ENGAGEMENT TERHADAP PERILAKU ETIS MAHASISWA SEBAGAI CALON TENAGA KERJA - Ni Putu Dera Yanthi; Putu Ayu Trisna Febrianty; Nyoman Dewi Pitaloka Cahyadi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2026)
Integrity challenges in academic and professional settings require universities to develop graduates who are not only competent but also ethically grounded as future workers. This study examines the effects of green psychological climate and student engagement on students’ ethical behavior. A quantitative survey design was employed using a five-point Likert questionnaire for the independent variables, while ethical behavior was measured dichotomously. Respondents were active undergraduate students (minimum fourth semester) selected through purposive sampling, totaling 384 participants. Data were analyzed using binary logistic regression, including model fit assessment, simultaneous and partial tests, and odds ratio interpretation. The results indicate that the model is adequate and that green psychological climate and student engagement significantly influence students’ ethical behavior both jointly and individually; student engagement shows a more dominant likelihood effect than green psychological climate. These findings highlight that students’ ethical behavior is shaped by the interaction between an institutional climate that consistently reinforces ethics and sustainability values and students’ active psychological involvement in learning. The study suggests strengthening campus policies on integrity and sustainability and implementing learning strategies that enhance engagement to support more sustainable prevention of unethical behavior.